Generic reassignment of Centropristis fuscula Poey, 1861 (Teleostei: Serranidae), with re-description of the species and comments on its geographical range and sexual system - Carvalho-Filho, Alfredo; Baldwin, Carole C.; Fischer, Luciano G.; Robertson, D. Ross; Bertoncini, Athila; Garcia, Lucas Canes; Silva, Jodir Pereira Da; Sampaio, Claudio L. S. (Zootaxa, 2023)
Centropristes fusculus Poey, 1861 historically has variously and somewhat perplexingly been assigned to Centropristis Cuvier, 1829, Prionodes Jenyns, 1840, and Serranus Cuvier, 1816. Here, we provide evidence from comparisons of morphology, ecology, and sexual systems for its inclusion in Serranus and redescribe the species based on the holotype and 60 specimens from Brazil, the Caribbean, the United States, and Uruguay. Serranus fusculus is a simultaneous hermaphrodite, a sexual system that is relevant to its generic placement. The inclusion of Serranus fusculus in the genus Serranus increases to 33 the number of currently valid Serranus species, of which two are found in the Western Indian Ocean, six in the eastern Pacific and 25 in the Atlantic Ocean (15 restricted to the western Atlantic and 10 to the eastern and Central Atlantic). An identification key to western Atlantic species of the genus is provided.